Developing Speaking Proficiency through Interview Projects: Insights from EFL Learner Experience and Classroom Practice - Maruanaya, Hendrik Jacob; Tuasella, Patrick; Camerling, Bella Claudia F.; Samsuri, Dian Faradila (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2025)
This study investigates This study investigates the perceived impact of the Student Interview Project (SIP) as a pedagogical tool in enhancing students’ speaking skill in a professional speaking class. Employing a mixed-methods approach, both qualitative and quantitative data were collected through classroom observations, questionnaires, and interviews with 12 undergraduate students. The findings indicate that SIP significantly improves students' confidence, fluency, and linguistic competence, while reducing anxiety and shyness. The project also fostered authentic communication and active engagement. The study concludes that interview project activities offer a practical and motivational learning strategy for developing professional speaking abilities.